2016
DOI: 10.1109/tcsi.2016.2525098
|View full text |Cite
|
Sign up to set email alerts
|

Time-Based Sensor Interface Circuits in CMOS and Carbon Nanotube Technologies

Abstract: The evolution of electronics towards compact and highly energy-efficient systems requires joint efforts in developing both innovative system architectures and novel devices. Recent developments show that time-based sensor interfaces yield highly-digital architectures, which are compatible with advanced silicon CMOS at highly-scaled technology nodes. Advancements in CMOS time-based sensor interfaces show that new circuit techniques can help to increase performance and robustness. Furthermore, these architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…In two other notable studies, time-based sensor interfaces [88] and transfer on biological surfaces [89] have been demonstrated. Briefly, time-based sensor interfaces enable robust, lowpower sensing that can be readily integrated with traditional digital systems.…”
Section: Swcnts In Sensing Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In two other notable studies, time-based sensor interfaces [88] and transfer on biological surfaces [89] have been demonstrated. Briefly, time-based sensor interfaces enable robust, lowpower sensing that can be readily integrated with traditional digital systems.…”
Section: Swcnts In Sensing Technologiesmentioning
confidence: 99%
“…Using 32 nm SWCNT technology (i.e., 32 nm minimum feature size), an integrated time-based IR sensor with a low supply voltage of 2 V has been shown to operate at ≈100 kHz with a low power consumption of 130 nW. [88] In another study, the bio-integration capabilities of flexible SWCNT-based electronics were demonstrated by fabricating high-performance SWCNT devices on a transferable substrate. Through a sacrificial layer approach, these devices have been successfully transferred to several irregular biological surfaces including a human wrist, a biodegradable polymer, and a curved plant leaf.…”
Section: Swcnts In Sensing Technologiesmentioning
confidence: 99%
“…1 (b) shows the cross-sectional view of the CNFET. The surface potential of the intrinsic channel, φS, is obtained by voltage dividing between the quantum capacitance per channel per unit length, Cq, given by (4), and the gate-channel electrostatic oxide capacitance per channel per unit length, Cox, as (5) [20].…”
Section: A Basis Of Cnfetsmentioning
confidence: 99%
“…They are utilized in the field-effect transistors (FETs) as an alternative to conventional channels to provide CNFET devices, being considered as promising devices that could be substituted for CMOS by continuing scaling trends in semiconductor technology in the future [1]. Despite the intensive researches on the CNFETs in digital circuits and applications [2]- [4], few works can be found on CNFET applications in analog and RF domain; some of them are limited to presenting the lumped model for CNFET structures as impedance matching components via metal contacts [5]; other studies have focused on the CNFET unity gain frequency, fT, as a RF property which is given by vF/(2πLg) for the Fermi velocity of vF and gate length of Lg [6], and also have performed CNFET device level considerations [7]. Moreover, RF building blocks features such as noise, linearity, power, and bandwidth have been reviewed in [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Frequency-based interface techniques can be found in a large variety of sensor readout systems, such as microwave chemical sensors [ 17 , 18 ], dielectric spectroscopy [ 19 , 20 ], Wheatstone-bridge resistive sensors [ 21 , 22 ], eddy-current sensors [ 23 ], magnetic sensors [ 24 ], and so forth. In the context of MEMS accelerometers, frequency-based methods can be realized using either mechanical or electrical resonators.…”
Section: Introductionmentioning
confidence: 99%